What Factors Determine the Production of Independent Smallholder Oil Palm? - Mirawati Yanita; Suandi (Talenta Publisher, 2021)
Oil palm is the most efficient crop in producing oil than other crops, such as soybean, rapeseed, and sunflower. However, the oil palm plantation of independent smallholders faced low productivity in terms of input used. This study aims to determine the production factors that influence independent oil palm smallholders in Kumpeh Sub-district, Muaro Jambi District. This research was conducted in three villages in Kumpeh, namely Mekarsari, Betung, and Seponjen. Samples consisted of 63 smallholders and were taken using the Simple Random Sampling method. The data were analyzed descriptively and subjected to statistical tests of multiple linear regression analysis. The results show an R2 of 0.888, indicating that the model variables can explain 88.8 percent of the oil palm production variation. The F test resulted in a value of 115.299, showing that the production variables together have a real effect on production. Partially, the independent variables that have a real and significant impact on oil palm production at a realistic level (Î±) of 5 percent are land area, fertilizer, and pesticides. At the same time, labor does not significantly affect palm oil production.